Research and practice on the main models and supporting technologies of ecological greenhouse agriculture in China - LI Pingping; HAN Jiangang; CHEN Xin; GAO Lihong (浙江大学学报. 农业与生命科学版, 2024)
Ecological greenhouse agriculture refers to an ecological farming model that utilizes clean, green, and healthy production methods for greenhouse planting and breeding. Its goal is to improve resource use efficiency, enhance agricultural product yield and quality, and promote environmental benefits. In China, there are two primary categories of ecological greenhouse agriculture (key promotion by the Ministry of Agriculture in 2002). The first category is the “four-in-one” ecological model combining crop planting, animal breeding, and biogas production within a greenhouse. It has evolved from individual family greenhouse facilities to village-based ecological greenhouse clusters, and then to industrialized biogas production from large-scale piggery, where pig manure is converted into biogas and integrated into the power grid. Biogas slurry is transported through pipelines to farmland, reducing the use of chemical fertilizers and improving soil quality. The system structure configuration, supporting technologies and equipments for planting and breeding are continuously being developed and improved. The second category is the ecological greenhouse agriculture model that adopts comprehensive ecological agricultural technologies. These technologies include various types of vertical and three-dimensional cultivation methods to increase land resource use efficiency, rotational cultivation technologies to reduce continuous cropping obstacles and pesticide usage in greenhouse vegetable production, healthy cultivation technologies involving the proper application of organic fertilizers to improve soil properties or the use of fermented agricultural and forestry wastes as organic substrate to provide nutrients to crops, ecological control technologies to reduce the occurrence of diseases, pests and weeds, such as insect-proof net covering, color board and light trap-killing, high-temperature sealing, steam disinfection, colored film covering soils, and biological control of natural enemy insects. It is expected that, through further research on related supporting equipments and technologies, the informatization and automation levels of ecological greenhouse agriculture can be improved, and thereby the sustainable development goal of greenhouse agriculture will be reached.